مكانة الشعر التعليمي في الأدب العرلي - Mahmud M. Ahmad Abdalwahid
Educational poetry is one of the types of general poetry which is governs by its rules and regulations and has flourished in the Umayyad and Abbasid era, i.e., in the second century A.H. with Raabah Ibn Al-Ajaj, and reached its peak at the end of the third century A.H. of the Abbasid era; as a result of the intellectual and financial luxury.The researcher has selected the section of Silent Non and Tanween from ( Mitin Tuhfat Alatfal Fi Tajweed Alqura'n) written by Shaikh Sulaiman Al-Jamzori as a practical model for the study. This is in order to highlight the value of educational poetry and its important contribution in Arabic literature. The researcher has utilized the historical deduction and the descriptive analytical approaches to identify the roots of educational poetry. The most significant findings of the study are that the educational poetry is mostly far away from passion. The study also showed that the educational poetry deals with a scientific issue such as grammar or rhetoric or historical issue such as legends, plays, wisdom, preaching, medicine, and philosophy, etc. In addition, the educational poetry can be applied to all what is known as the common moral and verbal types, and it is not limited to the meanings of words. Poets and scientists have competed in organizing the majority of sciences to facilitate the understanding and retention of the scientific materials. Finally, the researcher has recommended several recommedations including paying a particular attention to this type of poetry due to its importance to students and encourage students to learn and memorise it. It was also recommended that it is important to encourage scientists and poets to pay their attention to it and to develop the skills of those who are creative in this field by providing the important means for them.